Cupcake Friends - Ward, k.Deborah (USA)
Bess and Kim are best friends. Why are Bess and Kim best friends? Bess and Kim are cupcake friends. Bess and Kim are in the same class. Classmates must bring snacks to class$1! =s
Keywords: Juvenile Fiction; Literature